The effect of tropospheric delay on GPS height differences along the equator - Dodo, Joe; Md. Nor, Kamarudin; Yahya, Mohd. Hafiz (American Congress on Surveying and Mapping, 2008)
The fundamental issue in GPS positioning is the ability to mitigate all the potential errors and biases in the system. The atmosphere related errors of ionosphere and troposphere constitute one of these potential errors. The tropospheric effect is much more pronounced at the equatorial region due to its hot and wet conditions. This significantly affects the GPS signal due to the variability of the refractive index, which in turn affects the accuracy of GPS positioning, especially in the height components. This paper presents a study conducted in Malaysia located at the equatorial region, to investigate the impact of tropospheric delay on GPS height variation. Five GPS reference stations forming part of the Malaysian real-time kinematic GPS network (MyRTKnet) in johor were used. RINEX data from these stations were integrated with GPS and ground meteorological data observed from a GPS station located at the Universiti Teknologi Malaysia (UTM), at varying antenna heights for each session of observation in four campaigns with each campaign lasting for three days. A computer program called TROPO.exe was developed based on Saastamoinen tropospheric model. The result shows variations in the height component of GPS measurement with a maximum value of 119.100 cm and a minimum value of 37.990 cm. Similarly, the results show that the tropospheric delay is a distance-dependent error which varies with changes in meteorological condition. Furthermore, the results of simulated data show a decrease in tropospheric delay with increase in antenna height.